PERDAGANGAN SATWA LIAR DI PASAR TRADISIONAL DAN PASAR MODERN DI SULAWESI UTARA - Liana Liana; Witno Witno (Jurnal Penelitian Kehutanan BONITA, 2021)
Wildlife trade for consumption needs is found in various regions in Indonesia, one of which is in North Sulawesi Province. This animal trade spreads in traditional markets, including the Beriman Market in Tomohon which is also a domestic and foreign tourist destination, Langowan and Kawangkoan Markets in Kab. Minahasa. Karombassan and Bersehati Market in Manado City. Even the trade in wild animal meat has now entered modern markets in Manado City, which is the capital of North Sulawesi Province. This development of course threatens the preservation of biodiversity, especially endemic species. This study aims to determine the types of wildlife traded in North Sulawesi both in traditional and modern markets, to compare the price of wild animal meat in traditional and modern markets in North Sulawesi, and to determine the conservation status of traded wildlife species. There are 8 types of wild animals traded in traditional markets and 5 species in modern markets. The price of wild animal meat in the modern market is higher than in the traditional market. There was one endemic species that was traded, and 2 species that were listed in Appendix II of CITES.